Programa Mais Educação: avaliação do processo de implementação na Escola Municipal Casimiro Montenegro - Cunha, Elizangela Vale (2013)
The object of study in this research is the More Education Program, a public policy of comprehensive education through expansion of the times and places of learning established by the Ministry of Education (MEC). The study aims at evaluating the implementation process of the program, through the research study in a public school in Fortaleza - CE, therefore chosen as the locus Municipal School Casimiro Montenegro. We study different concepts and practices of holistic education, found in authors such as: Teixeira (1962), Paulo Freire (1968), Guara (2006), Cavaliere (2000), among others which motivated the research. We reflect on the concepts of comprehensive education present in subjects involved and analyze the school routine and the repercussion of More Education Program in the local community, and also relate to the intersectionality. The study assumes that the school alone can not fully develop their students. It is an evaluative study with a qualitative approach, which sought to include the voice of many subjects through interviews and focus groups, which were instrumental in data collection. It enabled to perceive the actions of the Program for the building of an intersectoral practice.